Mexico Needs a Fiscal Twist : Response to Covid-19 and Beyond - Hannan, Swarnali (IMF Working Papers; Working Paper, 2020)
Mexico's fiscal response to the pandemic has been modest compared to its peers, reflecting the authorities' desire to not issue new debt for spending. This approach, however, risks a more severe recession and a weaker economic recovery, with further costs in the future. Balancing the need for stronger near-term fiscal support for the people and the recovery against medium-term discipline, this paper lays out an alternative strategy. We show that credibly announcing a pro-growth and inclusive medium-term fiscal reform upfront-including increased tax capacity, higher public investment and strengthened social safety nets-would open space for larger short-term support and close medium-term fiscal gaps. Model simulations suggest that this package would boost output, limit lasting economic damage from the pandemic, and put debt trajectory on a declining path in the medium term as tax reforms pay off and risk premia decline.